Effect of Electrical and Electromechanical Stimulation on PC12 Cell Proliferation and Axon Outgrowth - Xu, Kailei; Liu, Xixia; Li, Xiaokeng; Yin, Jun; Wei, Peng; Qian, Jin; Sun, Jie (Frontiers in Bioengineering and Biotechnology, 2021)
Peripheral nerve injuries have become a common clinical disease with poor prognosis and complicated treatments. The development of tissue engineering pointed a promising direction to produce nerve conduits for nerve regeneration. Electrical and mechanical stimulations have been incorporated with tissue engineering, since such external stimulations could promote nerve cell proliferation, migration and differentiation. However, the combination of electrical and mechanical stimulations (electromechanical stimulation) and its effects on neuron proliferation and axon outgrowth have been rarely investigated. Herein, silver nanowires (AgNWs) embedded polydimethylsiloxane (PDMS) electrodes were developed to study the effects of electromechanical stimulation on rat pheochromocytoma cells (PC12 cells) behaviors. AgNWs/PDMS electrodes demonstrated good biocompatibility and established a stable electric field during mechanical stretching. PC12 cells showed enhanced proliferation rate and axon outgrowth under electrical stimulation alone, and the cell number significantly increased with higher electrical stimulation intensity. The involvement of mechanical stretching in electrical stimulation reduced the cell proliferation rate and axon outgrowth, compared with the case of electrical stimulation alone. Interestingly, the cellular axons outgrowth was found to depend on the stretching direction, where the axons prefer to align perpendicularly to the stretch direction. These results suggested that AgNWs/PDMS electrodes provide an in vitro platform to investigate the effects of electromechanical stimulation on nerve cell behaviors and can be potentially used for nerve regeneration in the future.